All stations! distress! : April 15, 1912, the day the Titanic sank - Brown, Don, 1949- (New York : Flash Point/Roaring Brook Press, 2008)
Provides the captivating story of this amazing vessel, the people who built it, and its tragic demise during its maiden voyage across the Atlantic as told through first-hand accounts and detailed illustrations of the events as they happened.
Presents the story of the Titanic, describing the people who built it and its tragic demise during its maiden voyage across the Atlantic, as told through first-hand accounts and detailed illustrations of the events as they happened.
Includes bibliographical references.
Keywords: Titanic (Steamship) -- Juvenile literature; Titanic (Steamship); Titanic (Steamship); Shipwrecks -- North Atlantic Ocean -- Juvenile literature; Shipwrecks -- North Atlantic Ocean; Shipwrecks